Green Supply Chain Management Performance in Timber Companies - Ermawati, Emmy; Bahtiar Sulistyan, Riza (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The aim of this study to determine the effect of waste treatment standards, the company's internal environment, and the company's external environment on Green Supply Chain Management at timber companies in Lumajang Regency. This type of research is quantitative by looking for causal relationships. The object of this research is a timber company in Lumajang Regency. The sampling technique used was Non Probability Sampling and the technique chosen was purposive sampling with a total of 70 respondents. As The independent variable consists of waste treatment standards, the company's internal environment and the company's external environment. The dependent variable is Green Supply Chain Management. The data analysis technique used is descriptive statistics with multiple linear regression analysis. The results of this study indicate that partially the waste treatment standards and the company's internal environment have a significant effect on Green Supply Chain Management, while the company's external environment partially has no significant effect on Green Supply Chain Management. Simultaneously, waste processing standards, company internal environment, company external environment have a significant effect on the Green Supply Chain Management of timber companies in the district.